Penerapan Hukuman Dalam Upaya Memperbaiki Ahklak Siswa di Sekolah SMPN 4 Kecamatan Guguak Kabupaten Lima Puluh Kota - Sovia Qulbi; Deswalantri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research is based on the application of punishment in improving students' morals, this is marked by the morals of students who like to come in when the teacher is explaining the lesson and also students who like to talk to friends when the teacher is explaining in front of the class, Abstract This study is motivated by the implementation of punishment as an effort to improve students’ moral behavior at SMPN 4 Guguak, Lima Puluh Kota Regency. The observed phenomena include students frequently leaving the classroom during lessons, talking with peers while the teacher is explaining, and displaying negative attitudes such as dishonesty, arrogance, betrayal, conceit, and envy. If such behaviors are ignored, students may fail to understand the importance of developing good character. The purpose of this study is to describe the forms of punishment applied by teachers to improve students’ morals. This research employed a descriptive qualitative approach, with teachers and students as the main informants and the principal as a supporting informant. Data collection techniques included observation and interviews, while data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that teachers implemented a series of measures, ranging from reminders, warnings, and reprimands to punishment as the final step. These punishments were intended to foster students’ awareness of the importance of good morals. The implication of this research is that educational punishment, when applied proportionally and accompanied by guidance, can serve as an effective tool for character development. Abstrak Penelitian ini dilatarbelakangi oleh adanya penerapan hukuman dalam memperbaiki akhlak siswa di SMPN 4 Kecamatan Guguak, Kabupaten Lima Puluh Kota. Fenomena yang ditemukan adalah masih banyak siswa yang keluar-masuk kelas saat guru menerangkan pelajaran, berbicara dengan teman saat pembelajaran berlangsung, serta menunjukkan perilaku yang kurang terpuji seperti berbohong, sombong, khianat, takabur, dan iri hati. Jika kondisi ini dibiarkan, siswa akan semakin jauh dari pemahaman tentang pentingnya memiliki akhlak yang baik. Tujuan penelitian ini adalah untuk mendeskripsikan bentuk penerapan hukuman yang dilakukan guru dalam rangka memperbaiki akhlak siswa. Jenis penelitian yang digunakan adalah deskriptif kualitatif dengan informan utama guru dan siswa, serta informan pendukung kepala sekolah. Teknik pengumpulan data meliputi observasi dan wawancara, sedangkan analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru menerapkan beberapa langkah mulai dari pemberitahuan, teguran, peringatan, hingga hukuman sebagai upaya terakhir. Hukuman tersebut digunakan untuk menumbuhkan kesadaran siswa tentang pentingnya akhlak yang baik. Implikasi dari penelitian ini adalah bahwa hukuman yang bersifat mendidik dapat berfungsi sebagai sarana pembinaan karakter siswa apabila diberikan secara proporsional dan disertai bimbingan. if this continues to be allowed then students will not understand the importance of having good morals, researchers feel it is very important to conduct research on the application of punishment in an effort to improve students' morals. The type of research used is descriptive qualitative, key informants are teachers and students and supporting informants are the principal. Data collection methods are observation and interview methods. Data analysis techniques used to examine all data, data reduction and data display. This study shows that students who come in and out when the teacher explains the lesson and talk when the teacher explains the lesson in the actions that the teacher will give to students are through notifications, reprimands, warnings and the last action taken by the teacher is to give punishment, and there are also forms of student morals that show the nature of lying, arrogant, betrayal, arrogance and envy with this the teacher will give punishment to students so that they can improve student morals into good morals by giving this punishment the teacher hopes that students will understand the importance of having good morals.